Histomorphological and Histochemical Studies on Caecal Tonsils of Kadaknath Fowl - Verma, Rakhi; Gupta, S. K.; Karmore, S. K.; Shukla, Supriya; Barhaiya , R. K. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Histomorphological and histochemical studies were conducted on the caecal tonsils of Kadaknath fowl at different age groups from day old to more than 32 weeks of age. The proximal dilated part of the caecum considered for caecal tonsil was composed of all four histological layers. The epithelium of mucosal villi was composed of simple columnar with goblet cells. The lymphatic tissue was present in the mucosa and submucosa of the caeca in the form of diffused and encapsulated lymphatic nodules. The number and size of encapsulated lymphatic nodule was increasing with the advancement of the age. The height of the mucosal villi was decreasing with the advancement of age whereas the lumen of the caeca was increasing with the advancement of age. PAS and AMPS activity was more in younger age groups than the older groups.
Keywords: Histomorphology; Caecal tonsil; Kadaknath; Fowl